2017
DOI: 10.4103/aam.aam_21_16
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric otorhinolaryngology emergencies at the Jos University Teaching Hospital: Study of frequency, management, and outcomes

Abstract: Background:Studies from Nigeria on pediatric otorhinolaryngology (ORL) emergencies are rare in literature with most focusing on emergencies involving individual systems.Objective:The aim of this study is to determine the prevalence of all ORL emergencies among children in our region to provide a baseline data for future health planning.Patients and Methods:This is a 1-year retrospective cross-sectional study of patients aged 16 years and below presenting to the Accident and Emergency Department of the Jos Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…Acute tonsillitis is an extensive inflammation of oropharyngeal lymph nodes, which are situated in the upper respiratory tract [1,2]. Acute tonsillitis in children has become one of the reasons for visits to the healthcare facilities in Nigeria [3,4]. Adoga et al [4] , in their study of otolaryngology emergencies in Nigeria, reported 63.5% were paediatric emergencies, among these emergency cases, 73.6% were children under 5 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute tonsillitis is an extensive inflammation of oropharyngeal lymph nodes, which are situated in the upper respiratory tract [1,2]. Acute tonsillitis in children has become one of the reasons for visits to the healthcare facilities in Nigeria [3,4]. Adoga et al [4] , in their study of otolaryngology emergencies in Nigeria, reported 63.5% were paediatric emergencies, among these emergency cases, 73.6% were children under 5 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Acute tonsillitis in children has become one of the reasons for visits to the healthcare facilities in Nigeria [3,4]. Adoga et al [4] , in their study of otolaryngology emergencies in Nigeria, reported 63.5% were paediatric emergencies, among these emergency cases, 73.6% were children under 5 years of age. Nigeria has a teeming population of children below 5 years of age, estimated at 31 million [5], which highlights the burden of acute tonsillitis in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Заболеваемость инфекциями в мире чрезвычайно высока как среди взрослых, так и среди детей. И если состояния с высоким риском смертности (например, бактериальный менингит, бактериальный эндокардит, сепсис, холера) встречаются относительно нечасто, то заболевания верхних дыхательных путей смело можно назвать лидирующими по обращению за медицинской помощью [1].…”
Section: Introductionunclassified
“…Одни вирусы вызывают заболевания преимущественно верхних дыхательных путей, другие -как верхних, так и нижних. Многообразие вирусов и большое количество различных штаммов каждого конкретного вируса обусловливают повторное развитие инфекций, затрагивающих преимущественно детей, особенно в возрасте до 5 лет [1].…”
Section: Introductionunclassified
“…Pediatric ORL-HNS emergencies are common in Nigeria too, yet many involve different diseases that require surgical intervention. 7 The causes are different for adults. Peripheral vertigo and otitis externa are the most common causes for referrals from the ED to ORL-HNS clinics.…”
mentioning
confidence: 99%